Study on Confined Compression Test of Coarse-grained Limestone Soil - WANG Qinyan; YAN Ming; LIANG Chunxiao; JIAO Longxin; SUN Yu (Renmin Zhujiang, 2020)
Taking the coarse-grained limestone soil as the research object, this paper carries out theconfined compression test for limestone soil with different coarse-grain content under 95%compaction and optimal moisture content, and studies the effects of P5 content and P2-5 content onengineering characteristics by analyzing the relationship curve between P5 content and P2-5 content and sedimentation, compression modulus and void ratio. The results show that: when theP5 content is less than 55%, the compression modulus increases slowly and the void ratio decreaseswith the increase of P5 content; when the P5 content is between 55% and 80%, the compressionmodulus increases rapidly and the void ratio almost doesn’t change with the increase of P5content;when P5 content is more than 80%, the compression modulus changes slightly and the voidratio increases rapidly with the increase of P5 content;with the increase of P2-5 content, theskeleton effect is enhanced and Es is obviously increased when P5 content is constant between 60%and 70%. The P5 content plays a leading role in the engineering characteristics of coarse-grainedlimestone soil within a certain range.